All in the mind? Pain, placebo effect, and ergogenic effect of caffeine in sports performance - Christopher J Beedie (Dove Medical Press, 2010)
Christopher J BeedieDepartment of Sports Science, Tourism and Leisure, Canterbury Christ Church, University, Canterbury, UKAbstract: The ergogenic effects of caffeine on performance are well documented. These effects are more evident in endurance and short-duration, sustained-effort events than in interactive or stop-go sports. Experimentally-induced placebo effects of caffeine on sports performance have also been observed in a number of recent studies. In the present paper it is argued that, given the nature of the sports in which caffeine effects are observed, the well documented hypoalgesic effects of caffeine, and the fact that pain is highly placebo-responsive, a reduction in perceived pain might be the common factor in both the biologic and placebo ergogenic effects of caffeine on sports performance. This idea is supported by evidence from medicine that suggests placebo effects are often associated with mechanisms similar or identical to those of the substance the subject believes they have ingested. Research findings from both biomedicine and sports medicine that attest to the interaction of biologic and psychologic factors in caffeine and pain responses are briefly reviewed. In conclusion, it is recommended that researchers investigate the pain hypothesis. Furthermore, researchers should consider psychosocial factors that might modulate the pain response as variables of interest in future caffeine and performance research.Keywords: caffeine hypoalgesia, nocebo effects, research methods